PENGARUH AIR RENDAMAN JERAMI PADA OVITRAP TERHADAP JUMLAH TELUR NYAMUK DEMAM BERDARAH (Aedes sp) YANG TERPERANGKAP - Putu Lili Ariani; I Nengah Suka Widana (FPMIPA IKIP PGRI Bali, 2016)
Influence Of Hay Infusion In Ovitrap To The Number Of Aedes Sp’s Eggs Trapped Control of the mosquito Aedes sp can be done with mechanical control is using ovitrap which already contain hay infusion. Hay infusion for a week will produce carbon dioxide gas, ammonia gas and octenol can stimulate the olfactory mosquitoes to lay eggs on ovitrap. This study aims to determine the effect of water immersion on ovitrap straw against dengue fever mosquito (Aedes sp) are trapped, and to know the concentration of the soaking water most excellent hay and obtain the maximum number of eggs of Aedes sp trapped. This study included experimental studies using completely andomized design with a pattern of